(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity and Religion: Education, Well-Being, Health and Conflict This paper represents a sketchy appraisal of human dignity from the perspective of religion, through the lenses of poverty, education, health and conflict. The author reflects on current data and on the general trends and attitudes that define what honors or dishonors a human being in the contemporary world.